ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KAROSERI DI KOTA PEKANBARU - Rimhot, Marpaung Sani Elizer; Rahmita, Budiartiningsih; Deny, Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the factors that influence the demand for car body in the city of Pekanbaru. In this study the population taken was the person who made a request for a car body in the city of Pekanbaru and used a sample of 84 respondents. This research uses accidental sampling technique. The analytical method used in this study is a quantitative descriptive method using SPSS software version 2.4. By using multiple linear regression to test the hypothesis. The results showed that the value of R squared was 0.757, which means that 75.7% of body demand in Pekanbaru City was influenced by the variable price of the goods themselves and consumer income while 24.3% was influenced by other variables. Simultaneous regression of independent variables has an influence on the dependent variable. Partially the price of the goods itself has a negative and significant influence on the demand for car body in the city of Pekanbaru. While the consumer income variable has a positive and significant impact on the demand for car body in the city of Pekanbaru.Keywords: Carrosery Demand, Price of Goods Itself, Consumer Revenue, Consumer Taste